A 1000 cc Intragastric Balloon for Weight Reduction. Issue 1 (1998) - Lavy, A.; Lachter, J.; Zinder, O.; Eidelman, S.
Abstract : Objective : To examine the efficiency of a 1000 cc intragastric balloon as an aid for weight reduction. Subject : Thirty-three morbidly obese persons, after multiple attempts for weight loss. Design : Intragastric 1000 cc balloons were endoscopically inserted into the stomachs of subjects. The balloons were left in place for six months. During that period the patients received dietary therapy. Hormone levels were measured prior to insertion and upon withdrawal of balloons. Results : After a brief initial weight loss, most patients regained the weight initially lost. Mean weight loss after six months was only 8 kg (range 0–22 kg). We found that Bombesin levels, but not Gastrin levels, were significantly lower at the end of therapy than before insertion of the balloon. Conclusion : We conclude that a large intragastric balloon for a prolonged time did not assist in weight loss. Our preliminary results show Bombesin levels change significantly, a finding which warrants further study.